Publication of Prussian Diplomatic Materials in the Sbornik Imperatorskogo Russkogo Istoricheskogo Obshchestva as a Tool of the Politics of History of the Russian Empire: Remarks on the Completeness of the Edition - Dukwicz, Dorota (Kwartalnik Historyczny, 2020)
At the turn of the nineteenth century many European states began to publish multi-volume editions of sources illustrating the political history of these states in previous centuries (for example, the Prussian Politische Correspondenz Friedrich’s des Großen). The Russian Sbornik Imperatorskogo Russkogo Istoricheskogo Obshchestva published by the Imperial Russian Historical Society is still used by researchers. It seems worthwhile to focus on the Sbornik and to assess its value as a scholarly edition using the Prussian diplomatic correspondence, included in that edition as a test-case.